Pengembangan Potensi Kelapa Untuk Mendorong Edukasi Berbasis Keterampilan Di Padukuhan Sorobayan - Alkayyisa, Frida; Fauzia, Gefira Afra; Ramadhani, Bumi; Al-Muhsi, Muhammad Hafizd; Hafizh, Faishal Nur; Dwianto, Fajar; Anggraini, Virliza Shafa; Wahyuning A, Charisma Yogi; Rahma, Annisa Aulia; Alifya, Yafi Rizal; Suswanta, Suswanta (Universitas Muhammadiyah Yogyakarta, 2025)
Sorobayan Hamlet is one of the hamlets located in Tirtorahayu Village, Galur, Kulonprogo which has great potential in the utilization of coconuts. Almost every house in this village has a coconut tree which makes it an abundant local commodity with various benefits. Coconuts can be processed into value-added products, such as coconut oil, as well as the use of coconut fiber as a liquid organic fertilizer. The purpose of this service is to provide education to the people of Sorobayan Hamlet regarding the right coconut cultivation techniques and how to process coconuts into high-value products in order to improve skills. The methods used in this service include socialization to the local community on how to increase coconut productivity, providing education on the right cultivation techniques, as well as practical training and assistance in processing coconuts into valuable products. The results of this service show a significant increase in the application of the right coconut cultivation techniques and improving community skills in utilizing local resources in Sorobayan Hamlet. By involving the community in utilizing the potential of local resources, this service is expected to provide new and beneficial education and skills for the community. This program is expected to be an example of empowerment that can be applied in other villages with similar potential